2004
DOI: 10.1007/s00281-004-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural endogenous adjuvants

Abstract: It has long been known that immunization with a protein by itself is often not sufficient to stimulate immunity, and may instead induce tolerance. To elicit productive immune responses exogenous adjuvants need to be co-injected with an antigen. One important class of adjuvants are the unique (non-mammalian) components of microbes. It is now believed that an adjuvant is required for immunity because the immune system evolved to respond to dangerous situations such as infections, and the presence of an adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 103 publications
0
122
0
1
Order By: Relevance
“…It was known that cells by themselves, including dead ones, could be immunogenic 9 , but whereas such findings were consistent with the model, there was no direct evidence that cellular immunogens actually contained adjuvant activity. However, it was subsequently shown that when dead cells were admixed with an antigen and injected into animals, they augmented antigen-specific CD4 + and CD8 + T-cell responses 10 11.…”
Section: The Danger Hypothesismentioning
confidence: 75%
See 1 more Smart Citation
“…It was known that cells by themselves, including dead ones, could be immunogenic 9 , but whereas such findings were consistent with the model, there was no direct evidence that cellular immunogens actually contained adjuvant activity. However, it was subsequently shown that when dead cells were admixed with an antigen and injected into animals, they augmented antigen-specific CD4 + and CD8 + T-cell responses 10 11.…”
Section: The Danger Hypothesismentioning
confidence: 75%
“…Thus, injury to one eye can initiate an autoimmune response that destroys the contralateral eye and ischemic necrosis of the heart can lead to an autoimmune pericarditis 16 17. In the case of tumours, injection of dead cancer cells can stimulate T-cell responses 9 . Moreover, killing tumour cells with chemotherapeutic agents in vivo can also lead to increased T-cell immunity 18 .…”
Section: Danger and Diseasementioning
confidence: 99%
“…Uric acid (UA) is a natural product of the purine metabolic pathway and is a principal endogenous danger signal released from injured cells (Rock, Hearn, Chen, & Shi, 2005; Shi, Evans, & Rock, 2003). The role of UA in the central nervous system (CNS) remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These endogenous activating molecules are collectively called damage-associated molecular pattern molecules (DAMPs) [27]. They include heat shock proteins (HSPs) [28], high mobility group box 1 protein (HMGB1) [29], β-defensin [30] and uric acid [31].…”
Section: Dendritic Cell Maturationmentioning
confidence: 99%